2017
DOI: 10.1152/ajpheart.00749.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning in pigs: a causal role for signal transducer and activator of transcription 3

Abstract: Ischemic preconditioning (IPC), i.e., brief episodes of nonlethal myocardial ischemia-reperfusion (I/R) before sustained ischemia with subsequent reperfusion, reduces infarct size in all species tested so far, including humans. In rodents, the cardioprotective signal transduction causally involves an activation of Akt, ERK1/2, and STAT3. However, there are apparent species differences in the signal transduction between rodents and larger mammals such as pigs, where data on IPC's signal transduction are inconsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
(49 reference statements)
8
29
0
Order By: Relevance
“…In pigs, RPER is mediated through an ATP-sensitive K ϩ channel-dependent mechanism and blocked by glibenclamide (32). In a very recent study from our laboratory, we found the infarct size reduction by RPER associated with increased phosphorylation of STAT3 during reperfusion (20) very similar to remote (34) and local (8) ischemic preconditioning and also to ischemic postconditioning (14). In that study, the protection by RPER became evident by an attenuation of ST segment elevation after the RPER procedure but during still ongoing coronary occlusion, indicating that RPER protects not only from reperfusion injury but also from ischemic injury (20).…”
Section: Introductionmentioning
confidence: 73%
“…In pigs, RPER is mediated through an ATP-sensitive K ϩ channel-dependent mechanism and blocked by glibenclamide (32). In a very recent study from our laboratory, we found the infarct size reduction by RPER associated with increased phosphorylation of STAT3 during reperfusion (20) very similar to remote (34) and local (8) ischemic preconditioning and also to ischemic postconditioning (14). In that study, the protection by RPER became evident by an attenuation of ST segment elevation after the RPER procedure but during still ongoing coronary occlusion, indicating that RPER protects not only from reperfusion injury but also from ischemic injury (20).…”
Section: Introductionmentioning
confidence: 73%
“…The algorithms for the cardioprotective maneuvers have been adapted from published maneuvers in clinical settings [IPC (Buyukates et al ), RIPC (Munk et al ), RPER (Bøtker et al ), POCO (Staat et al )] with slight modifications. These maneuvers robustly reduced IS in our prior studies (Skyschally et al ; Skyschally et al ; Gent et al ; Kleinbongard et al ). We therefore did not modify the algorithms in number and duration of ischemia/reperfusion cycles to further optimize the magnitude of IS reduction (Johnsen et al ).…”
Section: Limitation Of Methodssupporting
confidence: 62%
“…The underlying data were retrospectively analyzed from experiments performed in a single institution over a period of 6 years. Such approach has been used by others before (Rossello et al 2018) and is in line with the 3R (Skyschally et al 2013;Skyschally et al 2015;Gent et al 2017;Kleinbongard et al 2018). We therefore did not modify the algorithms in number and duration of ischemia/reperfusion cycles to further optimize the magnitude of IS reduction (Johnsen et al 2016).…”
Section: Limitation Of Methodsmentioning
confidence: 99%
See 2 more Smart Citations